CLINICAL EFFICACY OF RIZENDRONATE ACID IN THE COMPLEX THERAPY OF PATIENTS WITH OSTEOARTHRITIS AND METABOLIC SYNDROME - D. I. Lakhin; L. V. Vasilyeva (Медицинский вестник Юга России, 2017)
Objective: to assess the impact rizendronate acid on clinical and laboratory flow pattern of osteoarthritis in patients with the metabolic syndrome.Material and methods: the study included 50 patients with osteoarthritis and metabolic syndrome, which on the background of pathogenetic therapy received rizendronate acid at 35 mg per week during the year. Patients were evaluated indicators of inflammatory activity (ESR, CRP, TNF-α). The severity of articular syndrome was interpreted on a scale in rest and during movement, Lequesne index and WOMAC initially and after 3, 6 and 12 months. Mineral bone density (BMD) was assessed at lumbar spine by carrying out dual energy x-ray absorptiometry.Results: among patients receiving rizendronate acid was recorded a significant decline in CRP, ESR, TNF-α, positive changes in the indicators of the articular status – a significant reduction in the severity of pain at rest and in motion, decrease in Lequesne and WOMAC indexes, the trend of increase in BMD, while reducing the need for non-steroidal anti-inflammatory drugs.Conclusions: the use of risendronate acid in the complex therapy of patients with osteoarthritis with metabolic syndrome allows to achieve the reduction of the intensity of inflammation, the severity of pain while reducing the need for non-steroidal anti-inflammatory drugs.